Figurino em roda - Schwarz, Erika, 1986- (2023)
Abstract: Transcription of the recorded conversation about the scenographic processes carried out in the Scenic Creation Integrated Projects of the Department of Performing Arts at UNICAMP during the period of 2022. Based on the reports, notes about the methodology of costume in circle are presented – still in a state of research, part of the project "Scenographic urgencies: ecology, autonomy, historical intersections" by Erika Schwarz. The circle is summoned both in the creation and teaching practices and in the actual conversation event, in which is the orality that activates the memory of the creative body, allows the elaboration of ideas and the very production of knowledge